Estudo da interação de cobre com os suportes ZnO, TiO, e Nb2O5 e efeitos sobre a reforma do metanol - Machado, Nádia Regina Camargo Fernandes (1995)
To study the copper-zinc oxide interaction, Cu/ZnO, Cu/TiO2, Cu/Nb2O5 and Cu/Al2O3 catalysts were analysed and compared. TiO2 and Nb2O5 were chosen due to their n semiconductivity generating properties, similar to ZnO. On the other hand Al2O3 was chosen as a non-semiconductor support. In this way it was possible to verify the ZnO influence on the catalytic properties of Cu/ZnO catalysts. Two series of catalysts were prepared by impregnation. In one of them there was not copper enough to form a monolayer and the interaction would be exposed, catalysts B. In the other series there was enough copper to form two layers on the support. The interaction would be in the copper crystallite, catalysts A. The DRX analysis proved the good crystallinity of the catalysts. TPR, XPS and DRS proved that the interaction is formed in the calcination step with CuO and support oxide solution formation. This reduction may occur through copper, which is reoxidised, there being non-reduced copper occupying vacancies on the support. This explains the difficulty in the chemissorption tests observed in these catalysts. The catalysts were tested in the methanol reform reaction. With the Cu/Al2O3 catalysts where there is no interaction formation, the low copper concentration convert less methanol than the high concentration ones. In the catalysts where the copper support oxide interaction exists, the catalysts with low concentration are the ones which convert more. This shows that the active sites for the reaction are obtained through the interaction, which is more exposed in the catalysts with low concentration. The pure support oxides and CuO were also tested in the methanol reform reaction. Except Al2O3, all of them convert the methanol. The CuO presents the bigger conversion. Among the catalysts tested, Cu/ZnO are the ones that have the biggest conversion, showing that Cu-ZnO interaction is stronger than Cu-TiO2 and Cu-Nb205 producing more active sites.